2021
DOI: 10.1007/s11694-021-01078-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of xanthan, guar and tragacanth on quality and shelf life of hazelnut sauce: study with generalized regression, PCA and PLSR techniques

Abstract: Nut sauce can be used as a functional food substitute for mayonnaise. This study is thus aimed to investigate the effects of xanthan, guar and tragacanth hydrocolloids on the physicochemical properties and sensory characteristics of hazelnut sauce. For this purpose, various contents of the mentioned compounds (0, 0.25. 0.5, 0.75 and 1 g/100 g) were employed in the hazelnut sauce formulation. The moisture content, pH, acidity, viscosity, texture parameters, sensory specifications, and stability of the samples w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…The principal components matrix is the result of the eigenvector matrix based on the total variance. The goal of this method is to define and characterize the maximum variance with the smallest number of components (Habibi Najafi et al., 2019 ; Mahdavi‐Roshan et al., 2022 ; Pourfarzad & Taleb Derakhshan, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The principal components matrix is the result of the eigenvector matrix based on the total variance. The goal of this method is to define and characterize the maximum variance with the smallest number of components (Habibi Najafi et al., 2019 ; Mahdavi‐Roshan et al., 2022 ; Pourfarzad & Taleb Derakhshan, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…The goal is to explain as much of the total variance of the variables as possible, and the components are calculated as linear combinations of the original variables. Some authors have searched to correlate different properties of various products using PCA (Habibi Najafi et al, 2016;Manohar & Rao, 2002;Pourfarzad et al, 2012). TA B L E 3 Sensory changes in fermented fish sauce.…”
Section: Principal Component Analysismentioning
confidence: 99%
“…A higher amount of salts in the carrot sauce may be another reason for increasing of TA [ 26 ]. A study conducted by Pourfarzad & Derakhshan [ 27 ] on hazelnut sauce also showed that TA increased during storage while using guar gum and tragacanth as a thickening agent.…”
Section: Resultsmentioning
confidence: 99%